Photo-thermal nanoparticle hydrogel as well as preparation and application thereof in field of airway regeneration
By designing a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles, the inhibition of recurrent airway stenosis and airway hydrogel stability are solved, and the effects of anti-fibrosis, antibacterial and airway tissue regeneration are achieved.
Patent Information
- Application Number
- CN202411535576.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to effectively inhibit recurrent airway stenosis, especially pathological proliferation of fibroblasts, and airway hydrogels have not been effectively verified at the animal level, which has challenges of adhesion and stability.
Design and prepare a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles. The nanoparticles are formed by ultrasound, and the hydrogel fiber scaffold is prepared on a hydrodynamic draft spinning platform, combined with wet-meshing technology and reinforce the solution to ensure the stability and adhesion of the scaffold.
This hydrogel fiber scaffold can produce thermal effects under near-infrared light irradiation, inhibit fibroblast proliferation, significantly antibacterial, promote airway tissue regeneration, and significantly improve airway patency.
Smart Images

Figure CN119405887A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of bioengineering, and in particular to a photothermal nanoparticle hydrogel and its preparation and application in the field of airway regeneration. Background Art
[0002] Benign recurrent airway stenosis refers to airway lumen stenosis caused by endotracheal infection, mechanical stimulation or trauma, which is ineffective after repeated treatment. Patients experience progressive dyspnea, and in the late stage, irreversible airway obstruction, softening and collapse often occur, even leading to suffocation and death. Taking mechanical stimulation as an example, the rate of airway stenosis after endotracheal intubation is as high as 10% to 22%, of which fatal severe stenosis accounts for 2%, and the proportion of restenosis exceeds 28%. Against the background of an aging population, viral pandemics, and rising incidences of chronic respiratory diseases, the incidence of recurrent airway stenosis has increased year by year, bringing a heavy medical burden to patients, families and society.
[0003] The current clinical treatments for benign recurrent airway stenosis mainly include surgical treatment, interventional treatment, and drug treatment, but all of the above methods have clinical limitations: 1) End-to-end anastomosis reconstruction after surgical resection is an effective method for treating airway stenosis, but when the lesion is large, long-segment tracheal resection will increase the tension of the anastomosis and cause fatal complications; 2) Transbronchial interventional treatment is also the main treatment for airway stenosis, including ablation, cryosurgery, balloon dilatation, airway stent placement, etc., but these measures can often only relieve airway symptoms in the short term and are difficult to inhibit granulation proliferation. Patients need to repeatedly remove airway hyperplasia tissue throughout their lives to maintain respiratory function; 3) Anti-inflammatory and anti-fibrotic drugs such as triamcinolone acetonide and nintedanib are also used in the treatment of airway stenosis, but they can only temporarily improve symptoms or delay progression, and cannot cure it. Based on the above limitations, it is urgent to develop an effective treatment for recurrent airway stenosis to improve the quality of life of patients and keep them away from the risk of suffocation.
[0004] With the development of interdisciplinary disciplines, bioengineering technology has brought new ideas to solve the clinical dilemma of airway stenosis. Designing airway hydrogels with biological functions can repair the lesion area and prevent airway stenosis. Hydrogels can be placed through the bronchus, which is more in line with the general trend of minimally invasive surgery and has transformation potential. Among them, 1) Hamilton et al. and Varma et al. tried to extract and amplify autologous airway epithelial cells and implant them on biological scaffolds to construct airway hydrogels in order to rebuild the airway barrier, defend against external stimuli, and promote tissue repair (Hamilton NJI, Hynds RE, Gowers KHC, Tait A, ButlerCR, Hopper C, Burns AJ, Birchall MA, Lowdell M, Janes SM. Using a Three-Dimensional Collagen Matrix to Deliver Respiratory Progenitor Cells to Decellularized Trachea In Vivo. Tissue Eng Part C Methods 2019: 2(25): 93-102. Varma R, MarinAraujo AE, Rostami S, Waddell TK, Karoubi G, Haykal S. Short-Term Preclinical Application of Functional Human Induced Pluripotent Stem Cell-Derived Airway Epithelial Patches. ADV HEALTHC MATER 2021:10(21).); 2) Some studies have attempted to load peptides, cytokines or extracellular vesicles into airway hydrogels to regulate local airway inflammation and accelerate the migration of adjacent cells (She Y, Fan Z, Wang L, Li Y, Sun W, Tang H, Zhang L, Wu L, Zheng H, Chen C. 3D Printed Biomimetic PCL Scaffold as Framework Interspersed With Collagen for Long Segment Tracheal Replacement. Frontiers in Cell and Developmental Biology 2021:9. Hu C, Ji H, Gong Y, Yang X, Jia Y, Liu Y, Ji G, Wang X, Wang M.Wet-adhesiveγ-PGA / ε-PLL hydrogel loaded with EGF for tracheal epithelial injury repair. JMATER CHEM B 2023:11(36):8666-8678.Zeng T, Yuan P, Liang L, Zhang X, Zhang H, WuW. Cartilaginous Extracellular Matrix Enriched with Human Gingival MesenchymalStem Cells Derived “Matrix Bound Extracellular Vesicles”Enabled FunctionalReconstruction of Tracheal Defect.ADV SCI 2022:9(2).). .
[0005] At present, the use of hydrogels in clinical practice is mainly for trauma and traumatic infection. There is no hydrogel product designed for the airway as a treatment method in clinical practice. Most of the hydrogels used in clinical practice are composed of hydrophilic polymers, and their three-dimensional network structure can absorb a large amount of water and can also be used to carry drugs. Taking the commercialized Deshishu Hydrosorb hydrogel wound dressing as an example, it is a sheet hydrogel product. The main advantage of this hydrogel is that it contains 60% water, which can release water to the wound, promote wound healing, reduce scar formation and pigmentation, and relieve wound pain; at the same time, it can absorb exudate to form a gel, absorb a small amount of exudate and odor, and can be removed in one piece without leaving any residue. The longest use time is up to 7 days, painless and non-damaging dressing change, and high economy. Finally, the hydrogel transparent belt grid scale is a semi-permeable membrane, which is breathable, water-impermeable and bacteria-impermeable, which is convenient for observing and recording wounds. It does not need to be replaced frequently, which can reduce secondary damage to the wound. This hydrogel product is easy to use. After a simple disinfection of the wound on the skin surface, it can be directly applied to the wound on the skin surface for treatment.
[0006] Although the above-mentioned hydrogels have achieved certain therapeutic effects in wound repair on the skin surface, there is currently no effective hydrogel design for airway stenosis. At the same time, the design of hydrogel materials in the airway also has the following problems: 1) There is still no effective means to inhibit the pathological proliferation of fibroblasts, the mechanism of recurrent airway stenosis, so it is difficult to achieve a breakthrough in efficacy. 2) Although airway hydrogels can theoretically adhere well to the airway inner wall microenvironment, this method has not been verified at the animal level, and the particularity of the airway environment poses a challenge to the placement of hydrogels.
[0007] Chinese patent document CN115591026A discloses a hydrogel porous silica airway stent and its preparation method, using medical silica gel and porogen as raw materials, through molding process and dissolution process to prepare a porous silica airway stent with a development anti-displacement structure; then, the porous silica airway stent is placed in dopamine hydrogel to obtain a hydrogel porous silica airway stent. However, there is no report on a photothermal nanoparticle hydrogel and its preparation and application in the field of airway regeneration. Summary of the invention
[0008] The purpose of the present invention is to solve the clinical dilemma that recurrent airway stenosis is serious and difficult to cure. A new type of hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles with anti-fibrosis, antibacterial and tissue regeneration and repair properties is designed and prepared. The scaffold can adhere well to the microenvironment of the inner wall of the airway, inhibit airway stenosis and promote airway epithelial regeneration.
[0009] The first aspect of the present invention provides a method for preparing a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles, comprising the following steps:
[0010] (A) Synthesis of polyquercetin nanoparticles: The quercetin raw material was dissolved in an ethanol / deionized water mixed solution, wherein the volume ratio of ethanol to deionized water was 5:3, and the concentration of quercetin was 0.5 mg / mL; ultrasonic treatment was performed to form a clear solution, and the solution was adjusted to pH = 9.6 with ammonia water, and stirred at a constant temperature for 24 h; the collected brown liquid was diluted with ethanol and the solvent was removed by rotary evaporation to obtain polyquercetin nanoparticles;
[0011] In the preparation of polyquercetin nanoparticles, the concentration of quercetin is selected to be 0.5 mg / mL, ultrasound is used to form a clear solution, ammonia water is used to adjust the solution to pH = 9.6, and constant temperature stirring is performed for 24 hours. Under this condition, the synthesized polyquercetin nanoparticles can be suspended to form nanoparticles. Under conventional conditions, quercetin molecules contain a large number of benzene ring structures, which are not easy to form long-chain structures. Under this condition, it is easier to form long-chain structures, and under ultrasound, the nanoparticle molecules can be fully dispersed to avoid agglomeration, thereby synthesizing polyquercetin nanoparticles.
[0012] (B) Synthesis of hydrogel loaded with polyquercetin nanoparticles: polyquercetin nanoparticles are dispersed in deionized water and ultrasonically vibrated to obtain a polyquercetin nanoparticle solution with a concentration of 1 mg / ml; a spinning solution with a mass concentration of 2% dissolved in deionized water is slowly added during stirring, wherein the spinning solution is a mixed solution of sodium alginate and sodium carboxymethyl cellulose, wherein the mass ratio of sodium alginate to sodium carboxymethyl cellulose is 7:3; calcium chloride is slowly dissolved in deionized water to prepare a calcium chloride solution with a mass concentration of 3% as a coagulation bath solution; A preliminary 1cm×1cm square hydrogel fiber scaffold was prepared by a hydrodynamic stretch spinning platform and wet-laid web forming technology; next, silk fibroin, dopamine and calcium chloride were added to the deionized water solution to prepare a reinforcement post-treatment solution, in which the silk fibroin mass concentration percentage was 5%, the dopamine mass concentration percentage was 3%, and the calcium chloride mass concentration percentage was 3%; the post-treatment solution was evenly sprayed onto the surface of the preliminary hydrogel fiber scaffold and allowed to stand at room temperature for 24 hours to obtain a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles.
[0013] Carboxymethyl cellulose has strong hygroscopicity and excellent permeability. Adding it as a spinning solution can improve the solubility of sodium alginate, and improve the tensile properties and elongation of the mixed solution, reduce the friction between fibers, reduce fiber breakage, improve fiber strength, strengthen the maintenance of the hydrogel fiber scaffold morphology and maintain the suitability of its degradation rate in the body. At the same time, based on the particularity of the airway environment, ordinary hydrogels are very easy to absorb water and degrade, and fall off in the airway to form obstructions. After being reinforced with the above-mentioned specific concentration of silk fibroin, dopamine, and calcium chloride mixed solution, the swelling performance of the hydrogel fiber scaffold in the complex environment of the airway can be better guaranteed, so that it will not absorb water and swell under warm airflow and then fall off, etc. It can better adhere to the airway surface and perform repair functions with the slow release of polyquercetin nanoparticles.
[0014] A second aspect of the present invention provides a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles, which is prepared by the preparation method as described above.
[0015] A third aspect of the present invention provides a use of the hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles as described above in the preparation of a product for treating airway stenosis.
[0016] Furthermore, the product for treating airway stenosis is a product that inhibits airway stenosis and promotes regeneration of airway epithelium.
[0017] When the present invention is used, in clinical practice, the airway stenosis area is first located through a bronchoscope, and locally accumulated sputum and the like are removed with a negative pressure aspirator, the stent of the present invention is clamped with a biopsy forceps, and delivered to the stenosis area through a bronchoscope biopsy channel, and the angle of the biopsy forceps is adjusted so that the stent of the present invention can completely cover the airway stenosis area.
[0018] The present invention has the advantages that:
[0019] The present invention constructs a novel hydrogel fiber scaffold loaded with photothermal nanoparticles, and its functions include: 1) anti-fibrosis: photothermal nanoparticles can produce a thermal effect under the irradiation of near-infrared light zone II, thereby inhibiting the pathological proliferation of fibroblasts in situ, and further inhibiting the occurrence of airway stenosis; 2) antibacterial: the inside of the airway is a bacterial environment, which is very prone to infection when damaged. The thermal effect of polyquercetin photothermal nanoparticles can significantly resist bacteria; 3) promote tissue regeneration: the fiber network in the hydrogel can provide a skeleton for cells to cling to, promote the migration of healthy cells in adjacent tissues to the lesion area, and at the same time inhibit the local oxidative stress process in the airway, accelerating the regeneration process of airway tissue. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 .Schematic diagram of synthetic polyquercetin molecule;
[0021] Figure 2 .Synthesis of hydrogel;
[0022] Figure 3 .Photothermal effect and fibrosis effect of hydrogel;
[0023] Figure 4 .Antibacterial effect of hydrogel;
[0024] Figure 5 .The effect of hydrogel in promoting regeneration. DETAILED DESCRIPTION
[0025] The specific implementation methods provided by the present invention are described in detail below in conjunction with examples.
[0026] Example 1: Preparation of a novel hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles
[0027] (A) Synthesis of polyquercetin nanoparticles: The quercetin raw material was dissolved in an ethanol / deionized water mixed solution, wherein the volume ratio of ethanol to deionized water was 5:3, and the concentration of quercetin was 0.5 mg / mL. Ultrasound was used to form a clear solution, and the solution was adjusted to pH = 9.6 with ammonia water and stirred at a constant temperature for 24 hours. The collected brown liquid was diluted with ethanol and the solvent was removed by rotary evaporation to obtain polyquercetin nanoparticles ( Figure 1 ).
[0028] (B) Synthesis of hydrogel loaded with polyquercetin nanoparticles: The polyquercetin nanoparticles were dispersed in deionized water and ultrasonically vibrated to obtain a 1 mg / mL polyquercetin nanoparticle solution. During the stirring process, a spinning solution dissolved in deionized water with a mass concentration of 2% was slowly added. The spinning solution was a mixed solution of sodium alginate and sodium carboxymethyl cellulose, wherein the mass ratio of sodium alginate to sodium carboxymethyl cellulose was 7:3. Calcium chloride was slowly dissolved in deionized water to prepare a 3% calcium chloride solution as a coagulation bath solution. A preliminary 3 cm × 3 cm square hydrogel fiber scaffold was prepared by a hydrodynamic stretching spinning platform and wet web forming technology. Next, silk fibroin, dopamine, and calcium chloride were added to the deionized water solution to prepare a reinforcement post-treatment solution, wherein the silk fibroin mass concentration was 5%, the dopamine mass concentration was 3%, and the calcium chloride mass concentration was 3%. The post-treatment solution was evenly sprayed onto the surface of the preliminary hydrogel fiber scaffold and allowed to stand at room temperature for 24 hours to obtain a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles.
[0029] By utilizing the self-assembly effect, the present invention successfully prepared polyquercetin photothermal nanoparticles using quercetin monomer as raw material. The results of scanning electron microscopy showed that the nanoparticles were homogeneous and regular ( Figure 2 A). Then, using polyquercetin nanoparticles as raw materials, according to the above steps, a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles was synthesized ( Figure 2 B).
[0030] Embodiment 2:
[0031] 1) Anti-fibrosis: First, the photothermal conversion properties of polyquercetin photothermal nanoparticles were tested in vitro. The infrared camera showed that under the irradiation of near-infrared light in the second region, the hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles could significantly increase the temperature ( Figure 3 A).
[0032] Next, the photothermal anti-fibrosis effect of the hydrogel was verified in the rabbit airway epithelial injury model. The experimental rabbits were fasted and deprived of water 12 hours before surgery. Animal surgical instruments were sterilized with high-temperature and high-pressure steam 24 hours before surgery and dried for standby use. According to the instructions, Shutai 50 was prepared and administered at a dose of 10 mg / kg. The experimental rabbits were punctured by ear vein and injected with anesthetic drugs for general anesthesia. After reaching the ideal anesthesia state, the experimental rabbits were moved to the operating table, in a prone position, with their limbs fully fixed. After exposing the neck skin, disinfect it with iodine 3 times. Straighten the head of the experimental animal, touch and confirm the position of the trachea, and cut the skin longitudinally about 6 cm just above the trachea. With the assistance of an assistant, ophthalmic scissors were used to separate the subcutaneous, fascial and muscle tissues layer by layer to fully expose the trachea, but it was not necessary to completely free it. During the operation, it was separated along the tissue gap to avoid damaging blood vessels and muscles. Select the area of 5-6 cartilage rings under the thyroid cartilage, cut the experimental rabbit trachea with thick scissors but do not need to be completely cut off, use a biopsy brush to scrape off the 1.5cm long and 1cm wide airway epithelial defect, and adhere the polyquercetin photothermal nanoparticle hydrogel fiber scaffold to the epithelial defect. Anastomosis of the trachea was performed in an interrupted suture manner. Pour normal saline into the surgical incision, observe for 30 seconds to determine whether there is anastomotic leakage, add needle suture repair if necessary, and check again for leakage. Suture the muscle and fascia tissue layer by layer, and close the skin incision to complete the construction of the rabbit airway stenosis model and the loading of the hydrogel fiber scaffold. After surgery, the experimental rabbit neck modeling area was continuously irradiated with a wavelength of 808nm laser at a power of 1.8W for 5min every other day to study the in vivo photothermal repair performance of the non-woven fiber scaffold loaded with polyquercetin nanoparticles.
[0033] The results showed that the material still had a significant photothermal conversion effect in rabbits. At the same time, the results of postoperative bronchoscopy also showed that the airway stenosis of the rabbits was significantly suppressed and the airway lumen was unobstructed. ( Figure 3 B).
[0034] 2) Antibacterial: The antibacterial effect of the hydrogel under the photothermal effect was evaluated in vitro. Escherichia coli and Staphylococcus aureus were diluted with sterile PBS to a total bacterial colony count (CFU) per unit volume (unit: mL) of 1×10 6 100 μL of bacterial suspension was evenly spread on the agar plate, and then a 1 cm diameter disc of polyquercetin photothermal nanoparticle hydrogel material was placed on the agar plate. The plate was irradiated with a wavelength of 808 nm laser at a power of 1.8 W for 5 min every 6 h. After culturing at 37 ° C for 24 h, photos were taken and the diameter of the inhibition zone was recorded.
[0035] The results showed that after using near-infrared light zone II irradiation, the hydrogel fiber scaffold showed significant antibacterial efficacy, and the inhibition zone was significant compared with the control group, including the inhibition of Gram-positive bacteria and Gram-negative bacteria ( Figure 4 ).
[0036] 3) Promote tissue regeneration: In order to evaluate the airway tissue regeneration function at the animal level, the present invention established a rabbit airway stenosis model, and conducted hydrogel repair experiments and photothermal therapy, see 1) for details.
[0037] After 28 days of photothermal treatment, the experimental trachea area of the experimental animals was collected and tissue sections were prepared for HE staining. The results showed that the hydrogel photothermal treatment group showed good airway pseudostratified ciliated columnar epithelium regeneration and submucosal fibrosis inhibition, further proving the clinical efficacy of the hydrogel ( Figure 5 ).
[0038] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles, characterized in that: The following steps are involved: (A) Synthesis of polyquercetin nanoparticles: The quercetin raw material was dissolved in an ethanol / deionized water mixed solution, wherein the volume ratio of ethanol to deionized water was 5:3, and the concentration of quercetin was 0.5 mg / mL; ultrasonic treatment was performed to form a clear solution, and the solution was adjusted to pH = 9.6 with ammonia water, and stirred at a constant temperature for 24 h; the collected brown liquid was diluted with ethanol and the solvent was removed by rotary evaporation to obtain polyquercetin nanoparticles; (B) Synthesis of hydrogel loaded with polyquercetin nanoparticles: polyquercetin nanoparticles were dispersed in deionized water and ultrasonically vibrated to obtain a polyquercetin nanoparticle solution with a concentration of 1 mg / ml; a spinning solution dissolved in deionized water with a mass concentration of 2% was slowly added during stirring, wherein the spinning solution was a mixed solution of sodium alginate and sodium carboxymethyl cellulose, wherein the mass ratio of sodium alginate to sodium carboxymethyl cellulose was 7:3; calcium chloride was slowly dissolved in deionized water to prepare a 3% calcium chloride solution as a coagulation bath solution; a hydrogel fiber scaffold was prepared by a hydrodynamic stretching spinning platform and a wet-laid web forming technology; next, silk fibroin, dopamine, and calcium chloride were added to the deionized water solution to prepare a reinforcement post-treatment solution, wherein the mass concentration of silk fibroin was 5%, the mass concentration of dopamine was 3%, and the mass concentration of calcium chloride was 3%; the post-treatment solution was evenly sprayed onto the surface of the preliminary hydrogel fiber scaffold and allowed to stand at room temperature for 24 hours to obtain a hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles.
2. A hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles, characterized in that: It is prepared by the preparation method as claimed in claim 1.
3. Use of the hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles as claimed in claim 2 in the preparation of a product for treating airway stenosis.
4. Use of the hydrogel fiber scaffold loaded with polyquercetin photothermal nanoparticles according to claim 3 in the preparation of a product for treating airway stenosis, characterized in that: The product for treating airway stenosis is a product that inhibits airway stenosis and promotes regeneration of airway epithelium.
Citation Information
Patent Citations
Hydrogel porous silica gel airway stent and preparation method thereof
CN115591026A